Pengembangan Platform Internet Of Things (IoT) menggunakan komunikasi WebSocket: Internet Of Things (IoT) Platform Development using WebSocket communication - Kojansow, Charles William; Manembu, Pinrolinvic D. K.; Rumagit, Arthur M. (Jurnal Teknik Informatika, 2024)
This research focuses on developing a website-based Internet of Things (IoT) platform specifically for Sam Ratulangi University. The main objective is to design and develop a real-time IoT platform that can be accessed by students and university lecturers, with a limited scope of use for the Sam Ratulangi University academic community. This research identifies the need for developing a website-based IoT platform and effective ways to achieve real-time communication. The technology used includes Websocket for real-time data communication, a combination of REST API and WebSocket for communication efficiency, as well as the use of SQL and NoSQL databases tailored to the type of data to increase application performance. The results of this research show that the IoT platform developed runs smoothly and efficiently, with good data communication between devices and clients. The application of the selected technologies and methods has proven effective in supporting dynamic interactions between IoT devices and systems, as well as in achieving application development goals quickly and flexibly. This research contributes to enriching educational and research resources at universities, especially in the field of IoT technology.